2016
DOI: 10.7314/apjcp.2016.17.2.445
|View full text |Cite
|
Sign up to set email alerts
|

Understanding EGFR Signaling in Breast Cancer and Breast Cancer Stem Cells: Overexpression and Therapeutic Implications

Abstract: Epidermal growth factor receptors (EGFRs/HERs) and downstream signaling pathways have been implicated in the pathogenesis of several malignancies including breast cancer and its resistance to treatment with chemotherapeutic drugs. Consequently, several monoclonal antibodies as well as small molecule inhibitors targeting these pathways have emerged as therapeutic tools in the recent past. However, studies have shown that utilizing these molecules in combination with chemotherapy has yielded only limited success… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 67 publications
1
30
0
Order By: Relevance
“…The evidence for the impact of EGFR on survival and recurrence deserves to be explored in the Pakistani population as it suffers from a record high prevalence of OSCC and patients encounter inadequate diagnostic and treatment measures. EGFR has the potential to become a target for therapeutic measures in the form of monoclonal antibodies or tyrosine kinase inhibitors as has been the case for breast [28], colorectal and lung cancer [35]. As a result, improvement in patient prognosis and overall survival may be seen.…”
Section: Ivyspring International Publishermentioning
confidence: 99%
See 1 more Smart Citation
“…The evidence for the impact of EGFR on survival and recurrence deserves to be explored in the Pakistani population as it suffers from a record high prevalence of OSCC and patients encounter inadequate diagnostic and treatment measures. EGFR has the potential to become a target for therapeutic measures in the form of monoclonal antibodies or tyrosine kinase inhibitors as has been the case for breast [28], colorectal and lung cancer [35]. As a result, improvement in patient prognosis and overall survival may be seen.…”
Section: Ivyspring International Publishermentioning
confidence: 99%
“…It was concluded that EGFR was a significant independent determinant of survival and a strong predictor for locoregional relapse [24]. Various other cancers have also been found to harbour EGFR mutations and overexpression such as glioblastoma multiforme [25], lung cancer [26], head and neck squamous cell carcinoma [27], breast [28], colorectal [29] and oesophageal cancers [30] leading to a worse patient prognosis.…”
Section: Ivyspring International Publishermentioning
confidence: 99%
“…Cetuximab is a chimeric mAb targeting domain III of HER1 and approved for treatment of colorectal cancers (Table ). Due to its higher HER1binding affinity than TGF and EGF, following receptor binding, phosphorylation will be induced which can potentially lead to modification of biological responses, interfering with aberrant growth signals and/or triggering cell apoptosis . Furthermore, this mAb is capable of other classical antibody‐dependent cell‐mediated cytotoxicity (ADCC) or complement‐dependent cytotoxicity which improve the mAb therapeutic efficacy in treatment of malignant tumours .…”
Section: Anit‐her1 Mabs and Derivativesmentioning
confidence: 99%
“…Due to its higher HER1binding affinity than TGF and EGF, following receptor binding, phosphorylation will be induced [15][16][17][18] which can potentially lead to modification of biological responses, interfering with aberrant growth signals and/or triggering cell apoptosis. [10,19,20] Furthermore, this mAb is capable of other classical antibody-dependent cell-mediated cytotoxicity (ADCC) or complement-dependent cytotoxicity which improve the mAb therapeutic efficacy in treatment of malignant tumours. [21][22][23][24][25] In addition to these, cetuximab is the only effective mAb for relapse or metastatic cancers.…”
Section: Nimotuzumab (Theracim)mentioning
confidence: 99%
“…A number of techniques including immunohistochemistry (IHC), DNA microarray technology, fluorescent in situ hybridization (FISH) are utilized to reveal molecular differences within the same or different histopathological specimens [14][15][16]. Using IHC and DNA microarrays lead to the identification of five discrete subtypes of breast cancer.…”
Section: Molecular Classificationmentioning
confidence: 99%